Electrical and electrochemical measurements in nanostructured films of polythiophene derivatives - Braunger, Maria Luisa [UNESP]; Barros, Anerise [UNESP]; Ferreira, Marystela; Olivati, Clarissa de Almeida [UNESP] (Elsevier B.V., 2015)
Thin films from polythiophene derivatives can be fabricated by some experimental methods, including the Langmuir techniques, which are particularly suitable if some degree of molecular control is required. In this study, electrical and electrochemical measurements in Langmuir-Schaefer and spin-coated films of polythiophene derivatives were carried out in order to compare the influence of the deposition technique in these properties. Through cyclic voltammetry and UV-visible absorption measurements it was possible to estimate the energy diagrams for all the polythiophene films. Besides, electrochromic effect in the polythiophene thin films was observed. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Polythiophene; Langmuir-Schaefer; Electrical characterization; Energy diagram; Cyclic voltammetry